PENGARUH CITRA, KUALITAS RELASIONAL, DAN PERSEPSI NILAI TERHADAP SIKAP, LOYALITAS SERTA KEINGINAN UNTUK BERPINDAH PADA INDUSTRI CAFE DI YOGYAKARTA - Petra Surya Mega Wijaya (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
Recent rapidly growth industry in Jogjakarta is café. Café in which commonly open at night and tend to use the form of discothèque is now very popular among young people and young executives. Based on the phenomenon this research intends to observe and examine important factors which affect young people and young executive visiting such café. The dependent variables used in this research are customer’s loyalty and customer’s intention to switch into another industry like café. Furthermore, the independent variables are perception and brand image. Hence, the perception variable is believed affected by image, relational quality, and perception on value. The total observed data are 197 gathered from people who regularly visiting café for the last three months. The data will be analyzed using the Structural Equation Modeling (SEM). The result shows that perception on value is affected by perception, furthermore perception affect customer’s loyalty. The most important finding is that brand image and relational quality doesn’t affect customer’s perception. Moreover the intention to switch into another café and brand image doesn’t affect customer’s loyalty.Key words: Brand image, relational, perception on value, loyalty, intention to switch, café, and structural equation modeling.